Remote ischemic preconditioning in patients undergoing coronary bypass grafting following acute coronary syndrome without ST elevation - Miličić, Miroslav; Soldatović, Ivan; Nežić, Duško; Jović, Miomir; Maravić Stojković, Vera; Vuković, Petar; Milojević, Predrag (Vojnosanitetski pregled, 2021)
Background/Aim. A protection of heart and other organs from ischemic-reperfusion injuries can be provided by remote ischemic preconditioning (RIPC) by brief episodes of ischemia and reperfusion in distant tissues. The aim of this study was to assess effects of RIPC on early outcomes in patients underwent coronary bypass surgery (CABG) following acute coronary syndrome without persistent ST segment elevation (NSTEMI ACS). Methods. This trial included 42 patients randomized into two groups: the group 1 received RIPC and the group 2 was without RIPC (control group). Pre-, intra- and postoperative parameters were compared but primary endpoint was myocardial injury reflected as value of troponin I measured preoperatively and 1, 6, 12, 24, 48 and 72 h postoperatively. The secondary endpoints were hemodynamic parameters, blood loss, intensive care unit stay, mortality etc. Results. The groups 1 and 2 were similar in preoperative characteristics including age, New York Heart Association (NYHA) class, EuroSCORE II, left ventricular ejection fraction. The only significant difference between groups was for triple vessel coronary disease with dominance in the RIPC group [20 (100%) vs. 17 (77.3%), p = 0.049]. Cardiopulmonary bypass time [mean (± standard deviation): 83.0 (22.9) vs. 67.0 (17.4) minutes, p = 0.015], cross clamp time [57.9 (15.4) vs. 44.3 (14.3) minutes, p = 0.005] and number of conduits [median (25–75th percentile): 23.5(3–4) vs. 3(2–3), p = 0.002] were different. Other intra- and postoperative variables did not differ between groups. There were no differences in C reactive protein levels and postoperative hemodynamic parameters. Average troponin values in all time points revealed no significant differences between groups (p0h = 0.740, p1h = 0.212, p6h = 0.504, p12h = 0.597, p24h = 0.562, p48h = 0.465 and p72h = 0.715, respectively). Furthermore, there were no significant differences in adverse events, hospital stay and mortality between groups. Conclusion. Treatment with RIPC during CABG following NSTEMI ACS did not provide better myocardial protection and hemodynamics characteristics but further larger randomized studies are needed t. prove its real value.
Keywords: coronary artery bypass; ischemic preconditioning, myocardial; myocardial revascularization; non-st elevated myocardial infarction; troponon i; treatment outcome